Governance, Regulation and Powers on the Internet - Brousseau, Eric; Marzouki, Meryem; Méadel, Cécile (Cambridge University Press, 2012)
Digital technologies have prompted the emergence of new modes of regulation and governance, since they allow for more decentralized processes of elaboration and implementation of norms. Moreover, the Internet has been raising a wide set of governance issues since it affects many domains, such as individual rights, public liberties, property rights, economic competition, market regulation, conflict management, security and the sovereignty of states. There is therefore a need to understand how technical, political, economic and social norms are articulated, as well as to understand who the main actors of this process of transformation are, how they interact and how these changes may influence international rulings. This book brings together an international team of scholars to explain and analyse how collective regulations evolve in the broader context of the development of post-modern societies, globalization, the reshaping of international relations and the profound transformations of nation-states